Efficacy of Pre-Synchronization and CIDR on the Outcome of Short-TermSynchronization Program in Zandi Ewes During the Breeding Season - Reza Arjmandi; Mahdi Vodjgani; Amir Niasari Naslaji; Faramarz Gharagozlou; Vahid Akbarinejad (Iranian Journal of Veterinary Medicine, 2021)
BACKGROUND: Timed breeding programs are essential to implementing extensive artificial insemination (AI) programs in sheep. OBJECTIVES: This study aimed to evaluate whether application of pre-synchronization and controlled internal drug releasing (CIDR) before and during fixed time AI protocol, respectively, could enhance estrus synchronization and fertility of ewes. METHODS: A total of 120 ewes were randomly assigned into four experimental groups (n=30 in each group) considering age, weight, and body condition score (BCS). All ewes received GnRH (25 μg of alarelin acetate), and five days afterwards, PGF2α (75 μg d-cloprostenol) plus eCG (400 IU). In the control group, ewes received no additional treatment. In Pre-synch group, ewes received two injections of PGF2α at 9-day interval three days before GnRH administration of main estrus syn-chronization protocol. In CIDR group, ewes received 5-day CIDR between GnRH and PGF2α of main estrus synchronization protocol. In Pre-synch-CIDR group, ewes received both two injections of PGF2α at 9-day interval and 5-day CIDR. Blood serum progesterone concentrations were measured in all ewes prior to injection of PGF     2α (day 5). All ewes were subjected to fixed time laparoscopic AI 48 hours after administration of the last PGF     2α. RESULTS: No interaction was found between CIDR and pre-synchronization protocols (p >0.05). Progesterone concen-tration was higher in the CIDR groups than in groups without CIDR (p <0.0001). Estrous cycle was not affected by pre-synchronization and CIDR (p >0.05). The estrus was earlier in ewes with pre-synchronization compared to ewes without pre-synchronization following the last injection of prostaglandin (p =0.022). Pregnancy rate, lambing rate, prolificacy rate, fecundity rate, lamb weight at birth, and lamb gender were not significantly different between the treatment groups (p >0.05). CONCLUSIONS: In our study, estrus rate and reproductive parameters showed no significant differences between dif-ferent groups, although pre-synchronization advanced onset of estrus expression.